Practical Measures for Institutional Program Reviews: A Case Study of a Small Post-Secondary Institution - Jayachandran, John; Neufeldt, Colin; Smythe, Elizabeth; Franke, Oliver (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2019)
Post-secondary institutions carry out cyclical program reviews (CPRs) to assess educational effectiveness. CPRs often use both qualitative and quantitative data analyses with the aim of improving teaching and learning. Though most of the CPR review studies identify various factors for this purpose, they fail to identify measures/indicators that are relevant and practical for the institutional decision-making process. Our main objectives for this article are two-fold: first, we identify and list variables that are measurable and sort them into clusters/groups that are relevant to all programs, and second, we critically assess the relevance of these indicators to program review in a small-sized, post-secondary institution.